Emenda Constitucional 103/19 e a redução do valor da pensão por morte no Regime Geral de Previdência Social: uma análise à luz do princípio da confiança - Sousa, Priscila Machado de Almeida Duarte de (2023)
The present dissertation is about the constitutionality of the calculation of the death benefit after the Constitutional Amendment nº 103/19 in the Regular Social Security System. The Reform in Social Security System drastically reduced the value of the death benefit; the pension that, before, was calculated with a coefficient of 100%, now has a coefficient, depending on the case, of 36%. The article 201, V, of the Federal Constitution of 1988, provided for the social protection of the family, due to the death of its mainteiner, and the drastic reduction of the benefit’s value reduces the protection of the rule. The analysis of the constitutionality of the legal prediction will be based on the principle of trust